Landau level spectroscopy of PbSnSe topological crystalline insulator - Kristupas Kazimieras Tikuišis; Wyzula, Jan; Ohnoutek, Lukáš; Cejpek, Petr; Uhlířová, Klára; Hakl, Michael; Faugeras, Clément; Výborný, Karel; Ishida, Akihiro; Veis, Martin; Orlita, Milan (arXiv.org, 2021)
We report on an infrared magneto-spectroscopy study of Pb\(_{1-x}\)Sn\(_x\)Se, a topological crystalline insulator. We have examined a set of samples, all in the inverted regime of electronic bands, with the tin composition varying from \(x=0.2\) to \(0.33\). Our analysis shows that the observed response, composed of a series of interband inter-Landau level excitations, can be interpreted and modelled using the relativistic-like Hamiltonian for three-dimensional massive Dirac electrons, expanded to include diagonal quadratic terms that impose band inversion. In our data, we have not found any clear signature of massless electron states that are present on the surface of Pb\(_{1-x}\)Sn\(_x\)Se crystals in the inverted regime. Reasons for this unexpected result are discussed.